Perbedaan Morfologi Kelapa Sawit Lahan Basah dan Kering sebagai Penyusunan Leaflet Edukasi di Kabupaten OKU - Ashiddiqi, Afif Rifqy; Putri, Rossanita Truelovin Hadi; Meishanti, Ospa Pea Yuanita (YASIN, 2025)
Differences in environmental conditions between wetland and dryland areas are presumed to affect the morphological characteristics of oil palm (Elaeis guineensis Jacq.) in Ogan Komering Ulu (OKU) Regency, South Sumatra, in both vegetative and generative growth, while in-depth studies on the morphology of fruits, stems, and leaves across these two land types remain limited. This study aimed to describe the morphological differences of oil palm grown on wetland and dryland sites and to develop the findings into a contextual educational leaflet as a learning medium. A descriptive qualitative approach was employed through field observations in Airwall Village and Markisa Village, Lubuk Batang Subdistrict, OKU, with purposive sampling of productive and healthy oil palm plants. Data were collected through direct observation, interviews, and documentation, and were analyzed descriptively. The results show that oil palm grown on wetland areas has larger fruits with bright orange coloration, taller and more slender stems, and dense dark green leaves as a consequence of relatively optimal water and nutrient availability; conversely, oil palm on dryland exhibits smaller and duller fruits, shorter stems, and yellowish-green leaves that reflect drought stress and nutrient deficiency. These morphological findings were then packaged in the form of a contextual educational leaflet that visually compares plant characteristics in the two land types as an engaging, practical, and environmentally based biology learning medium. The study concludes that environmental conditions have a marked influence on oil palm morphology and that the findings have the potential to be utilized as innovative teaching materials in contextual biology learning in schools.